Research on quantitative method of GIS partial discharge. Issue 3 (March 2020) - Yang, Junting; Yang, Peipei; Zhang, Guangdong; Bao, Yanyan; Zhang, Hang; Ma, Zhenqi; Wen, Dinjun
Abstract: Optical method is a commonly used method for detecting partial discharge in electrical equipment. How to use photometric quantitative detection is one of the most urgent problems to be solved. Based on the in-depth analysis of the physical meaning of the integral value of the PD optical signal, it is concluded that the linear integral value of the signal is linear with the apparent discharge. The experimental results show that the integral value of the PD photometric signal at different polarities and different distances is linear with the apparent discharge. The larger the gap distance between the needle and the plate electrode is, the larger the slope is. The linear relationship between the average primary integrated value of the PD photometric signal and the average apparent discharge is different. With the increase of the applied voltage, the PD discharge intensity and the pulse repetition rate increase, and the phase interval of the PD becomes wider. The actual air gap volume of the PD becomes larger, and the variation interval becomes wider, that is, the apparent discharge amount distribution interval becomes wider, and the maximum value and the minimum value of the distribution interval become larger. Therefore, it is possible to obtain the PD apparent discharge amount by using the photometric signal, and it is effective and feasible to quantitatively detect the internal PD of the GIS by optical method.